Asymmetric supercapacitors based on Co, Ni and polypyrrole pseudocapacitive electrodes - Cai, Xiaoyi (2016)
Firstly, cobalt hydroxide nanowires network were grown on nitrogen doped microwave exfoliated graphite oxide OsJMEG). The specific capacitance can reach 610 F/g. Asymmetric pseudocapacitor devices were fabricated with Co(OH)2^IMEG as the positive electrode and polypyrrole(PPy)/rG-0 as the negative electrode. The Co(OH)2ANMEG//PPy/rG-O asymmetric supercapacitor have a high energy density of 24.9 WhTcg, significantly higher than a number of other devices fabricated and tested under the same measurement condition. PPy/rG-0 is proven to be a superior negative electrode to be used with transition metal based electrodes with narrow voltage window for supercapacitor devices. Secondly, Ni-Co-S and polypyrrole on vertically-aligned carbon nanotubes array (VA- CNTs)/3D carbon fiber paper (CFP) are developed as freestanding electrodes for supercapacitors. The binder-free asymmetric supercapacitor devices with Ni-Co-S/VA- CNTs/CFP as the positive electrode and polypyrrole/VA-CNTs/CFP as the negative electrode respectively demonstrates high energy density of 82 WMcg at 200 W/kg.